The relationship between smart cities and the internet of things in low density regions - Lopes, Isabel Maria (2018)
In these times of digital transformation, cities have overcome the challenges of the past and are building the future. The use of technological resources as a means of efficiently delivering various services and improving citizens’ quality of life has transformed regions and cities into smart regions and cities. There have been a remarkable amount of projects implemented by the Municipalities in the last years, taking the technologies to the cities. However, for a project to be interesting, it must have a positive impact on society, that is, citizens. This evidence gave rise to the present study whose goal was to find out if citizens living in inner cities, labeled as smart cities, actually consider them that way, and whether their city uses innovative solutions that optimize their daily lives. The results are discussed in the light of the literature and future work is identified with the aim of shedding some light on a field as emerging, promising and current as this of Intelligent Cities and the Internet of Things.